Bonding strength of steel rebars perpendicular to the hardened 3D-printed concrete layers. (18th July 2022) - Aramburu, A.; Calderon-Uriszar-Aldaca, I.; Puente, I.
Highlights: Tests on passive rebar bonding strength within 3D-printed mortar structures. 3D-printed concrete reinforcement applied perpendicularly to horizontal layers. Post-hardening reinforcement of 3D-printed concrete shapes. Standardized procedure to estimate adherence stress within 3D-printed specimens. Bonding strength development of rebars within 3D printed mortars at different ages. Abstract: Passive rebars are inserted into interior hollow channels within a 3D-printed mortar geometry and then bonded with a wet joint of filling mortar, in order to test the bonding strength of the rebars within the mortar structure. Standardized test procedures are adapted for the test procedure. The test results revealed bonding strengths with shear stresses within an interval between 16.75 MPa and 18 MPa, dependent upon rebar diameter, and good early strength development of the bonding mortar of at least 14 MPa during the first week. No specimen failed because of debonding between the filling mortar and the 3D-printed cylinder, nor because of debonding of the cylinder and the concrete poured around its exterior.